Therapeutic Efficacy of Carvedilol and Hawthorn Extract in Management of Dilated Cardiomyopathy in Dogs - K., Basava Reddy; C., Ansar Kamran; P.T., Ramesh; H.A., Upendra; Rao, Suguna; V., Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was undertaken to evaluate the effect of carvedilol and hawthorn extract in managing dilated cardiomyopathy  (DCM) to limit the treatment cost and improve the quality of pet life. Total 165 dogs were subjected to detailed clinical and physical examination, electrocardiography and echocardiography. Out of 165 dogs, 61(36.96%) were diagnosed as DCM, out of which 30 were  allocated randomly to three treatment groups comprising ten dogs in each group. Group-I dogs were treated with pimobendan, digoxin, enalapril and furosemide. In Group-II and III, pimobendan was replaced with carvedilol and hawthorn extract, respectively. Dogs with ventricular arrhythmias (Ventricular Premature Complexes, Ventricular fibrillation) were excluded from the treatment groups  as digoxin is contraindicated in ventricular arrhythmias. A noticeable improvement in clinical signs, thoracic radiographic findings, left  ventricular dimensions and left ventricular contractility indices was observed in the three treatment groups after 28 days of treatment  when compared to the pre-treatment values. The drug's therapeutic efficacy was evaluated based on comparative assessment of post treatment left ventricular contractility indices (fractional shortening and ejection fraction). Group I had longer survival time with mean of 375 ± 14.25 days followed by Group III (264.67 ± 41.22 days) and Group II (214.57 ± 31.32 days) dogs.
Keywords: Dilated Cardiomyopathy; Dogs; Pimobendan; Carvedilol; Hawthorn Extract